(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
Nonalcoholic fatty liver disease (NAFLD) and fibrosis are two of the most common liver diseases worldwide, with a rising incidence due to the increasing prevalence of obesity and metabolic syndrome. Early diagnosis and treatment are essential to prevent the progression of these conditions to more severe liver diseases. MicroRNAs (miRNAs) are small non-coding RNAs that play a crucial role in the regulation of gene expression and have emerged as promising biomarkers for the early diagnosis and monitoring of NAFLD and fibrosis. This review article provides an overview of the role of miRNAs in the pathogenesis of NAFLD and fibrosis, the potential of miRNAs as biomarkers and therapeutic targets for these conditions, and the current state of research in this field. The article also discusses the primary risk factors for NAFLD and fibrosis and the stages of these conditions that can be identified through the use of non-invasive imaging techniques and serum biomarkers, including miRNAs. Finally, the article provides recommendations for future research and the implications for clinical practice, highlighting the potential of miRNAs for improving the early diagnosis and treatment of NAFLD and fibrosis.